Embedding the value of natural capital into food: a bet for local policies in marginal areas - Angelo Martella; Francesca Pietrangeli; Elisa Biagetti; Barbara Pancino; Silvio Franco (Bio-based and Applied Economics)
This paper focuses on the correlation between socioeconomic marginality and environmental sustainability. These two concepts are at the chore of the international and European policy agenda, but they are not often merged in one action. Within this study, we selected a marginal area in central Italy and assessed its environmental sustainability, using the method of the ecological balance. The results show that this territory has the capacity to provide an amount of natural capital greater than the ecological footprint generated by local production activities, thus the value of the ecological balance is positive. Then, we discussed how local policies can favor processes focused on agricultural products coming from areas recognized as sustainable. Environmental sustainability can be work as a branding strategy, which can raise the market value of the products and the farmers’ income, thus supporting the economic development of marginal areas and promoting the protection of their natural capital.